تأثير التقليم الأخضر في جودة ثمار الدراق صنف »May flower« - دندة, علاء (Latakia University Journal -Biological Sciences Series, 2018)
The study was conducted in a farm in Tartous, during the years (2016) on the peach trees of age (8 years) at the named May flower planted RIA drip irrigation in a way, trees way goblet inlaid on the original seed of peaches for type Persica vulgaris planted at a distance (5 × 5) m within the orchard peach area (4) acres in order to study the effect of pruning green in fruit production and quality. -Winter pruning was conducted at the end of January (2016) in all the transactions were carried out in the green pruning (March 15, March 30, April 15, April 30). -The most important results that have been reached following: - Increased fruit diameter, where the fruit diameter arrived in (April 15) treatment to (5.3) cm compared with the witness, who stood fruit diameter (4.5) cm this increases the size of the fruit and thus improve the quality of marketing. - Increased fruit weight as it reached (171.3) g in trim (April 30) compared to the control ((150.1 g). - Increased fruit content of total dissolved solids and was (12.73%) compared to the control (11. 5%). - Fruit content of total sugars increased, amounting to (8.74%) compared to the control (8.62%). - Increased maturity coefficient reaching (3.59%) compared to the control (3.14%). أجريت الدراسة في مزرعة الحنفية من محافظة طرطوس عام (2016) م على أشجار دراق بعمر (8) سنوات من صنف مدخل يدعى May flower مزروعة ريا بالتنقيط على مسافة (5×5)م ضمن بستان دراق مساحته (4) دونم , الأشجار مرباة بالطريقة الكأسية مطعمة على الأصل البذري للنوع Persica vulgaris بهدف دراسة تأثير التقليم الأخضر في جودة ثمار هذا الصنف. أجري التقليم الشتوي في نهاية كانون الثاني من عام(2016)م في جميع المعاملات, وتم تنفيذ التقليم الأخضر في (15 آذار,30 آذار,15 نيسان,30 نيسان). أهم النتائج التي تم التوصل إليها مايلي: - ازداد قطر الثمرة, إذ وصل قطر الثمرة في معاملة (15 نيسان) إلى (5.3) سم مقارنة مع الشاهد الذي بلغ قطر الثمرة (4.5) سم وهذا يزيد من حجم الثمرة وبالتالي تحسين نوعيتها التسويقية. - ازداد وزن الثمرة, إذ وصل إلى ( 171.3)غ في تقليم (30 نيسان) مقارنة مع الشاهد ((150.1 غ . - ازداد محتوى الثمار من المواد الصلبة الذائبة الكلية وبلغ (%12.73) مقارنة مع الشاهد (%11.5). - ازداد محتوى الثمار من السكريات الكلية إذ بلغ (8.74%) مقارنة مع الشاهد (8.62%). - ازداد معامل النضج حيث وصل إلى (3.59%) مقارنة مع الشاهد (3.14%).